War Injuries of External Male Genitalia: A Prospective Single-Center Study from the General Military Hospital, Sana’a, Yemen (2022–2024) - Alsaqaf, Wael; Alkohlany, Khaled; Alshami , Majdi; Shaif , Mahmood; Al-Sakkaf, Abdullah; Farei, Ahmed; Shamsan, Aziz; Albaddai, Nasser (ASIDE Health Sciences, 2026)
Background: War-related external male genital injuries are uncommon but clinically significant, often coexisting with severe pelvic, vascular, and musculoskeletal trauma and causing potential long-term functional, cosmetic, and psychological effects.Methods: This prospective, single-center study at the General Military Hospital, Sana’a, Yemen, included all consecutive male patients presenting with war-related external genital injuries from April 2022 to March 2024. Minor isolated injuries were managed in the emergency department, while severe or associated injuries required admission. Data collected included injury mechanism, management, complications, and short-term outcomes. Primary outcomes were injury patterns, management strategies, and one-month clinical outcomes. Secondary outcomes included complications, erectile function, cosmetic acceptability, and semen analysis at one month.Results: Fifty-two patients (mean age 23.3 ± 4.9 years) were included. Penetrating trauma occurred in 44 (84.6%) and blunt trauma in 8 (15.4%). Penile injuries were seen in 16 (30.8%) and testicular injuries in 46 (88.4%). Isolated genital injuries occurred in 20 (38.4%), with 32 (61.5%) having associated injuries. All patients underwent surgery for penetrating wounds, large hematomas, or hematoceles. At one-month follow-up, early complications occurred in 12/52 patients, including wound infections (15.4%) and urinary tract infections (7.7%). Of 42 patients completing investigations, semen analysis was normal in 71.4%, and 28.6% had abnormal semen parameters. Late complications included testicular atrophy (33.3%), erectile dysfunction (4.8%), and post-operative penile curvature (4.8%).Conclusion: Prompt assessment and timely surgical management are essential. While most patients had satisfactory short-term outcomes, a notable proportion experienced complications, highlighting the need for structured protocols and longer follow-up.